IMPROVING ENGLISH PRESENT TENSES COMPREHENSION BY USING ENGLISH-DUBBED ANIME YU-GI-OH ARC-V - Aswir; Sabiq, Afif (English Education:Journal of English Teaching and Research, 2020)
The research aims to analyze the improvement of English Present Tense comprehension through visual material such as Japanese Animation Dubbing Series (JADS) or English-dubbed animation. Another purpose of this research is to help teacher on designing creative and fun technique for learning English Grammar. The research was conducted in SMAN 6 Tangsel and 30 students of both control and experimental classes were selected as sample of research. The researcher used purposive sampling technique and conducted both pre-test and post-test to gather the research data. While the control class used conventional technique on learning English Present Tense, the experimental class was using JADS on learning the Tenses. The research lasted for three weeks and researcher used compare the results of pre-test and post-test through SPSS 22. After analyzing the data through statistic method Paired-samples T-test, the t-value of experimental class is 9.180 and the value also becomes positive due to statistic formula. Then, the df is still 29 so t-value of df is 2.462. As the t-value of experimental class is higher than t-value of df (9.180>2.462). Because of the results of these T-values through Paired-samples T-test, researcher concludes that using visual material such as JADS for students in the classroom is effective to improve their comprehension for present tenses.